Cloning of the gene encoding Streptococcin A-FF22, a novel lantibiotic produced by Streptococcus pyogenes, and determination of its nucleotide sequence. - Hynes, W L (1993)
Streptococcin A-FF22 (SA-FF22) is a lantibiotic produced by Streptococcus pyogenes FF22. The nucleotide sequence of the SA-FF22 structural gene (scnA) was determined and shown to encode a 51-amino-acid prepeptide. The proteolytic processing site of the SA-FF22 prepeptide differs from that which characterizes other type A lantibiotics.